A model for handling overloading of literature review process for social science - Shah , Asadullah; Khowaza, Khamran; Shah, Abdul Salam (2015)
Literature review is an excruciating part in the process of research. It requires an analysis of published material on the topic of interest. Moreover, for a few researchers, it is challenging to extract a great number of required objectives, including problem identification, commonly known as 'gap' in research. Searching and locating most appropriate literature is no more great deal in this era of Information and Communication Technology (ICT), instead overloading of the literature is a major problem and the great challenge to be handled. Often postgraduate research students raise three questions to their peers and supervisors. First, how many articles are sufficient for a good for a good literature reviews? Second, how many past years literature will be enough to meet the required level for a good literature review? And third, what if, literature referred is published in the language other than researchers language? In this research paper a novel hypothetical model is proposed to answer first two questions; the number of articles required for a good and reasonable literature review and number of years backward the analysis of articles required for the same. Our results indicate that analysis of data partially support our hypothetical model and its assumptions.